Machine learning and Systems Approaches in Relation of Helicobacter pylori To Ageing Diseases - Kumari, D. Santosh; Kaladhar, DSVGK (International Journal of Computer Sciences and Engineering, 2025)
Helicobacter pylori is one of the bacterial pathogen showing great effect and associations with ageing diseases. The complex data prediction was done with Weka software. When compared with data distribution between Males and Females in relation with class H.pylori, it is shown that females are more prone to ageing diseases (especially gastric and Obesity). Cluster Centroids method was predicted with more chances for people in Urban regions with family history suffers gastric, expiry due to heart stoke with gastric, drink tea, with tension and stress. AD Tree shown positive for H.pylori (N) showing stomach pain, family suffered previously and Age >29.5. Subset Evaluator method was shown that Stomach pain, Aging diseases and smoking are the attributes associated with H.pylori. The highest accuracy for the data was predicted with random Forest and K Star followed by J48, Bayes Net, Naive Bayes, LMT and Simple Cost